The Indian Hyalopeplini (Insecta, Heteroptera, Miridae, Mirinae): A preliminary review - Yeshwanth, H. M.; Chérot, F. (Zootaxa, 2018)
The tribe Hyalopeplini of the subfamily Mirinae (Insecta, Heteroptera: Miridae) from India is reviewed. Five genera and ten species are cited from the country, keyed, illustrated and diagnosed. Hyalopeplinus malayensis Carvalho in Carvalho & Gross, 1979 is cited for the first time from India.